A COMPARATIVE STUDY OF DIGITAL LATERAL CEPHALOGRAM AND VIRTUAL CONE-BEAM COMPUTED ASSISTED CEPHALOGRAM IN CEPHALOMETRIC ANALYSIS - Qadeer, Momna; Nazir, Rozina; Arshad, Ruhamaa (Journal of Ayub Medical College Abbottabad, 2025)
Background: The Advent of innovative technologies like Cone Beam Computed Tomography (CBCT) scans presents itself as an alternative to traditional lateral cephalometric radiography. However, it is imperative to validate images generated using this technology for meaningful comparisons. Moreover emphasizing the necessity to justify the amount of radiation exposure is crucial. Through this investigation, we seek to determine the comparability of angular and linear measurements derived from Digital lateral cephalometry and CBCT derived lateral cephalograms. Methods: 40 lateral cephalometric radiographs and 40 virtual cephalograms from cone-beam computed tomography were analyzed, involving forty patients from the Orthodontic Department at Fauji Foundation Hospital Islamabad. After the prior calibration, two sets of measurements within a fifteen-day interval using Down’s analysis and WebCeph software. The discrepancies between these measurements were assessed to determine their significance Results: There was strong correlation between the measurements of 2D and 3D cephalometric angles among FA, AOC, MPA, YA, COP, IIA, IOPA, IMPA and UIAP Linear . The most notable variance was observed in the Cant of occlusal plane (COP) reaching a statistical significance (P < 0.05). Conversely, Y-axis exhibited the least variance. Conclusions: The absence of statistically significant differences suggests that, in our study, choice of radiograph used for analysis had minimal impact on the cephalometric measurements. These findings highlight the reliability and comparability between CBCAC and DLC.